THE EFFECTIVENESS OF CINEMA THERAPY-BASED COGNITIVE BEHAVIOR THERAPY GROUP COUNSELING APPROACH TO REDUCE DECADENCE OF MORAL BEHAVIOR - Cita Hermitha Noor Halimah; Purwati Purwati; Lianasari Lianasari (Prosiding University Research Colloquium, 2021)
This study aims to examine the effectiveness of group counseling with Cinema Therapy-Based Cognitive Behavior Therapy approach to reduce the decadence of adolescent moral behavior. This research is a pure experimental research using a model Pretest-PosttestControl Group Design.The subjects of this study were selected randomly. The samplestaken in this study were 10 adolescents consisting of 5 adolescents as the experimentalgroup and 5 adolescents as the control group. The data collection method was carried outusing a decadence questionnaire of adolescent moral behavior. The data analysis methodused in this study namely by using One way Anova Parametric Statistical analysis withthe help of SPSS For Windows version 24. The results showed that the group counselingapproach Cognitive Behavior Therapy Based on Cinema Therapyeffective in reducing thedecadence of adolescent moral behavior. This is evidenced by the results of the One-wayANOVA Parametric Statistics test with a probability of sig. (2-tailed) 0.007 <0.05. Basedon the results of the analysis and discussion, there is a difference in the average score ofthe decadence questionnaire on adolescent moral behavior between the experimentalgroup and thethe average value (9.18%) which is higher than the control group with anaverage increase (5.59%). The results of the study can be concluded that groupcounselingCinema Therapy-Based Cognitive Behavior Therapy approach is effective inreducing the decadence of adolescent moral behavior.